The Russian Military Intervention in Syria: Background, Causes and Consequences - Hossain, Ishtiaq (Al Zaytouna Centre for Studies and Consultations, 2015)
On September 30, 2015, Russian fighter aircraft based in Latakia, Syria, started bombing the forces opposed to President Bashar Al-Assad in the Syrian cities of Hama, Homs and the outskirts of Latakia. This is for the first time since the end of the Cold War that the Russian military have been in action anywhere in the Middle East. As reported in various media outlets if Russian troops are indeed deployed at a later date in Syria, then it would also be the first time since the 1970s that Russian military officers are stationed in the Middle East. The involvement of Russian military in the Syrian civil war is fraught with consequences for Syria itself, the region and the international arena. This paper purports to explain the causes, and consequences of Russian military involvement in Syria not only on the Syrian civil war but also on the regional and international politics.